Survival after surgery for acute type A aortic dissection in octogenarians - Fiore, Antonio; Lega, Javier Rodriguez; Buech, Joscha; Mariscalco, Giovanni; Perrotti, Andrea; Wisniewski, Konrad; Pinto, Angel G; Demal, Till; Rocek, Jan; Kacer, Petr; Gatti, Giuseppe; Vendramin, Igor; et al. (Journal of geriatric cardiology, 2024)
OBJECTIVE: To evaluate the benefits of surgical repair acute type A aortic dissection (ATAAD) on survival of octogenarians. METHODS: Patients who underwent surgery for acute ATAAD from the multicenter European Registry of Type A Aortic Dissection (ERTAAD) were the subjects of the present analysis. RESULTS: 326 (8.4%) patients were aged ≥ 80 years. Among 280 propensity score matched pairs, in-hospital mortality was 30.0% in patients aged ≥ 80 years and 20.0% in younger patients (P = 0.006), while 10-year mortality were 93.2% and 48.0%, respectively (P < 0.001). The hazard of mortality was higher among octogenarians up to two years after surgery, but it became comparable to that of younger patients up to 5 years. Among patients who survived 3 months after surgery, 10-year relative survival was 0.77 in patients aged < 80 years, and 0.46 in patients aged ≥ 80 years. Relative survival of octogenarians decreased markedly 5 years after surgery. Age ≥ 85 years, glomerular filtration rate, preoperative invasive ventilation, preoperative mesenteric mal-perfusion and aortic root replacement were independent predictors of in-hospital mortality among octogenarians (AUC = 0.792; E:O ratio = 0.991; CITL = 0.016; slope = 1.096). An additive score was developed. A risk score ≤ 1 was observed in 68.4% of patients, and their in-hospital mortality was 20.9%. CONCLUSIONS: Provided a thoughtful patient selection, surgery may provide a survival benefit in patients aged ≥ 80 years with ATAAD that, when compared to younger patients and the general population, may last up to 5 years after the procedure. These findings have significant epidemiologic and clinical relevance because of the increasing longevity of the population of the Western countries.